Describing adolescents with disabilities' experiences of COVID-19 and other humanitarian emergencies in low- and middle-income countries: a scoping review - Brigitte Rohwerder; Sara Wong; Shraddha Pokharel; Dipesh Khadka; Niraj Poudyal; Sagar Prasai; Nir Shrestha; Mary Wickenden; Joanna Morrison (Taylor & Francis Group, 2022)
Background The COVID-19 pandemic and other humanitarian emergencies exacerbate pre-existing inequalities faced by people with disabilities. They experience worse access to health, education, and social services, and increased violence in comparison with people without disabilities. Adolescents with disabilities are amongst those most severely affected in these situations. Using participatory research methods with adolescents can be more effective than other methods but may be challenging in such emergency contexts. Objectives We conducted a scoping review to: 1) describe the literature and methods used in peer-reviewed and grey literature on adolescents (aged ten to nineteen) with disabilities' experience of COVID-19 and other humanitarian emergencies in low- and middle-income countries, and 2) identify research gaps and make recommendations for future research. Methods The review followed a protocol developed using PRISMA guidelines and the Arksey and O'Malley framework. We searched grey and peer-reviewed literature between 2011 and 2021. Results Thirty studies were included. Twelve were peer-reviewed, and of those seven used participatory methods. Humanitarian emergencies had adverse effects on adolescents with disabilities across health, education, livelihoods, social protection, and community participation domains. Surprisingly few studies collected data directly with adolescents with disabilities. Twenty-three studies combined data from non-disabled children, caregivers, and disabled adults which made it challenging to understand adolescents with disabilities' unique experience. Conclusions Our review highlights both the scarcity of literature and the importance of conducting research with adolescents with disabilities in humanitarian contexts. Despite challenges, our review shows that it has been possible to conduct research with adolescents with disabilities to explore their experiences of humanitarian emergencies, and that these experiences were different from those of non-disabled adolescents. There is a need to disaggregate findings and support the implementation and reporting of rigorous research methods. Capacity development through partnerships between non-governmental organisations and researchers may improve reporting of methods.